2022
DOI: 10.1021/acsami.1c17860
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Gas Diffusion Electrode Fabrication for Electrochemical CO2 Reduction Using Physical Vapor Deposition Methods

Abstract: Electrochemical CO 2 reduction (ECR) promises the replacement of fossil fuels as the source of feedstock chemicals and seasonal storage of renewable energy. While much progress has been made in catalyst development and electrochemical reactor design, few studies have addressed the effect of catalyst integration on device performance. Using a microfluidic gas diffusion electrolyzer, we systematically studied the effect of thickness and the morphology of electron beam (EB) and magnetron-sputtered (MS) Cu catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…In the same study, however, the wetting angle of a 300 nm EB npAu coating (∼59°) was significantly smaller than that of the corresponding 300 nm EB pure Au coating (∼106°) prepared on a GDL . The more hydrophobic character of the 300 nm EB Au coating (∼106°) compared to our 400 MS Au coating (∼20°) is consistent with our previous work on EB and MS Cu coatings where we observed that the wetting angle on 400 nm EB Cu coatings (∼124°) is much higher than that of the corresponding 400 nm MS Cu coatings (∼65°), which makes the latter more prone to electrode flooding at high current densities . The different wetting behavior seems to be related to the different surface morphologies produced by EB and MS techniques with a more well-defined faceted nature of EB Cu coatings compared to the very rough and serrated appearance of MS Cu coatings .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the same study, however, the wetting angle of a 300 nm EB npAu coating (∼59°) was significantly smaller than that of the corresponding 300 nm EB pure Au coating (∼106°) prepared on a GDL . The more hydrophobic character of the 300 nm EB Au coating (∼106°) compared to our 400 MS Au coating (∼20°) is consistent with our previous work on EB and MS Cu coatings where we observed that the wetting angle on 400 nm EB Cu coatings (∼124°) is much higher than that of the corresponding 400 nm MS Cu coatings (∼65°), which makes the latter more prone to electrode flooding at high current densities . The different wetting behavior seems to be related to the different surface morphologies produced by EB and MS techniques with a more well-defined faceted nature of EB Cu coatings compared to the very rough and serrated appearance of MS Cu coatings .…”
Section: Resultsmentioning
confidence: 99%
“…The coatings are very uniform in thickness and have the same mesoscale porosity and nanoscale morphology consisting of faceted, 50–100 nm wide primary particles that form larger agglomerates which grow in size with increasing film thickness (Figure S1b,d). In general, while the morphologies of the MS Au and Ag 0.7 Au 0.3 coatings are very similar to that of the MS Cu catalyst coatings studied in our previous work, the MS Au coatings exhibit a more faceted appearance than the corresponding Cu MS coatings …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite significant prospect, the electrochemical CO 2 reduction reaction (CO 2 RR) encounters many challenges associated to high energy barriers, multiple parallel reactions and competitive hydrogen evolution reaction (HER) ( Yin et al, 2019 ). Consequently, a wide range of chemicals such as carbon monoxide (CO), formate (HCOO − ), methane (CH 4 ), methanol (CH 3 OH), ethane (C 2 H 6 ), ethylene (C 2 H 4 ) and ethanol (C 2 H 5 OH) is identified as the CO 2 RR products, and the formation of H 2 is almost inevitable in aqueous electrolytes ( Bagger et al, 2017 ; Zhao et al, 2018 ; Ren et al, 2019 ; Zeng et al, 2021a ; Zeng et al, 2021b ; Jeng et al, 2022 ; Zhou et al, 2022 ). Among these species, CO and its mixture with H 2 (H 2 /CO syngas) have high relevance for the chemical industry ( Nielsen et al, 2018 ; Zeng et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%